Amina - Cadidjato Baldé (Universidad de Alicante, 2019)
In this story, the author describes how a girl travels from her country of origin, an African country where the prospects were not too good for the personal and professional growth of women, until Seville (Spain) where she reaches a very successful achievement important for her that feels very satisfied: graduate in nursing.